COST EXPORT BRIQUETTES IN MALUKU : WITH ABC SYSTEM METHOD - Erly Leiwakabessy; Trisna Sary Lewaru; Fanny Monica Anakotta (RADJA PUBLIKA, 2025)
In Maluku, the basic material for making briquettes is very abundant but has not been utilized to become an export product. For this reason, this study tries to calculate the export costs for briquettes in Maluku using the ABC system method. The research method used is descriptive analysis with data from field and literature studies. Based on the study's results, it is known that to calculate export costs using the ABC method, all activities that occur in processing products and activities needed to export must be known. From the calculation results, the total cost required to produce and export briquettes based on the ABC system method is IDR—298,867,000.00 per container.